2021
DOI: 10.3390/ijms22157946
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Pyroptosis Augments Post-Transplant Survival of Stem Cells and Cardiac Function Following Ischemic Injury

Abstract: The acute demise of stem cells following transplantation significantly compromises the efficacy of stem cell-based cell therapeutics for infarcted hearts. As the stem cells transplanted into the damaged heart are readily exposed to the hostile environment, it can be assumed that the acute death of the transplanted stem cells is also inflicted by the same environmental cues that caused massive death of the host cardiac cells. Pyroptosis, a highly inflammatory form of programmed cell death, has been added to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…miRNAs are powerful molecules for the evaluation of clinical samples. Recent studies have suggested their novel potential as a diagnostic biomarker of cancer [40,41], obesity [42,43], brain disease [44,45], and heart disease [46][47][48][49]. However, using miRNAs for clinical applications still poses challenges that need to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are powerful molecules for the evaluation of clinical samples. Recent studies have suggested their novel potential as a diagnostic biomarker of cancer [40,41], obesity [42,43], brain disease [44,45], and heart disease [46][47][48][49]. However, using miRNAs for clinical applications still poses challenges that need to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hydrogen improved cardiac function and reduced the area of cardiac fibrosis by inhibiting NLRP3-mediated pyroptosis, and it has been demonstrated in vitro that hydrogen alleviated cardiomyocyte damage induced by hypoxia and myocardial fibroblast migration and activation induced by Ang II ( 121 ). As an important regulator of IL-1β production and subsequent pyroptosis, delivery of exogenous miRNA-762 before transplantation significantly increased the post-transplant survival of stem cells and also significantly ameliorated cardiac fibrosis and heart functions following I/R injury ( 120 ). Mesenchymal stem cells (MSCs), derived from bone marrow, placenta, adipose, or other tissues, significantly alleviated cardiac arrest cardiac injuries in swine, in which the protective effects were related to the inhibition of cell pyroptosis and ferroptosis ( 122 ).…”
Section: Potential Clinical Applications Of Pyroptosis To Ameliorate ...mentioning
confidence: 99%